Transparent reporting of research results in eLife - Teare, M Dawn (eLife, 2016)
Manuscripts should include all the experimental and statistical details that are needed to replicate the experiments and analyses reported in them.
Keywords: statistical design; reproducibilty; experimental design; scientific publishing; peer review; transparency